Tingkat Pengetahuan Mahasiswa Fakultas Farmasi Universitas Pekalongan Terhadap Swamedikasi Acne Vulgaris (Jerawat) - Dewi Rahma Febriyanti; Nila Oktaviani (Jurnal Ilmiah Kedokteran dan Kesehatan, 2023)
Acne is a skin condition that can be treated with self-medication using over-the-counter drugs (non-prescription drugs). The purpose of this study was to determine the level of knowledge of students of the Faculty of Pharmacy, University of Pekalongan about acne self-medication. This type of research is descriptive with a cross-sectional design. The research subjects were selected by stratified random sampling. Collecting data through a questionnaire that has been tested for validation by previous researchers. Respondents answered a questionnaire containing 16 questions online using the google form. Based on the results of the study, respondents had good to sufficient information on acne self-medication. Based on the results of the analysis, 52.29% of respondents had "good" knowledge and 47.05% of respondents had "adequate" knowledge about acne self-medication. Thus it can be seen that most students of the Faculty of Pharmacy, University of Pekalongan have good knowledge about acne self-medication as indicated by the proportion in the "good" category.